Wyzwania i pułapki w badaniu historiograficznego „życia po życiu” księcia z XIII wieku. Refleksje w związku z książką Pawła Żmudzkiego - Tomaszek, Michał (1972– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
In historiography, Leszek the Black, a prince in Krakow in the late thirteenth century, acquired the fame of a ruler victorious in wars with external enemies and a reputation for being entangled ininternal conflicts. His fame contributed to the fact that, in the sixteenth century, Polish heraldic legends associated the origins of a numer of noble coats of arms with Leszek. The historiographic image of the ruler through the centuries is the subject of Paweł Żmudzki’s book, the content of which is discussed in this article. The review highlights the advantages of the approach, which is focused on examining the narratives and the plot threads contained in them. The comments concern possible additional explanations of the positive image of Leszek the Black in sixteenth-century historiography and problems related to the methodology applied by the monograph’s author.
p. 143-160
Concerns book: Dux fabulosus : O tradycji historiograficznej osnutej wokół postaci Leszka Czarnego od "Gesta Lestkonis" do dzieł Bartosza Paprockiego / Paweł Żmudzki. - Warszawa : Wydawnictwa Uniwersytetu Warszawskiego, 2023.
Summary in English.
Keywords: Leszek the Black; Gryfina; Bolesław V the Chaste; Bartosz Paprocki; Polish historiography - 16th c.; Leszek Czarny, Duke of Kraków, approximately 1240-1288; Gryfina (Duchess of Kraków; after 1244-before 1309); Bolesław V, Wstydliwy, King of Poland; (1226-1279); Paprocki, Bartłomiej (ca 1543-ca 1614)